In Situ Crystallization of the Inorganic Lead-Free Halide Double Perovskite Cs2AgBiBr6 via Spray-Drying - Fett, Bastian; Kabaklı, Özde Ş; Sierra, Camila A.R.; Schulze, Patricia S.C.; Yoon, Songhak; Herbig, Bettina; Glunz, Stefan W.; Goldschmidt, Jan Christoph; Sextl, Gerhard; Mandel, Karl (ACS Applied Energy Materials, 2023)
Nontoxic, all-inorganic perovskite light absorbers have received a great deal of attention in recent years due to their potential to replace lead-containing perovskite materials in photovoltaics. Herein, the synthesis of the lead-free double perovskite Cs2AgBiBr6 as a powder, obtained via spray-drying, is reported to be capable of paving the way toward large scale production. Upon drying of the atomized precursor solution during spray-drying, the double-perovskite phase forms by in situ crystallization. The product that is obtained from spray-drying is compared to the one that is obtained from the so-called solution cooling method, which is often used for the absorber synthesis before dissolving the double perovskite powder for the thin film deposition. The absorber powder gained from the solution cooling method sets the benchmark for the spray-dried absorber powder. XRD and Raman analyses confirm the phase purity of the double perovskite, whereas UV-Vis spectroscopy confirms the desired bandgap. Furthermore, the absorber powders from both synthesis methods are successfully used to deposit and integrate absorber films in single-junction perovskite solar cells. Besides being introduced as an alternative synthesis route for the preparation of double perovskite absorber as dry powders independently from being applied onto a given substrate, the superior advantages of spray-drying compared to the conventional synthesis of the perovskite absorber via the solution cooling method are outlined: Spray-drying not only enables the synthesis of large amounts of perovskite absorber powders but also discards the usage of precarious solvents like concentrated hydrobromic acid and thus eliminates the need for extensive safety precautions. Hence, spray-drying may help the perovskite technology take the next step toward large-scale production and commercialization.
CRIS-Team Scopus Importer:2023-04-28
Keywords: Cs; double perovskite; lead-free; perovskite solar cells; spray-drying